Instantaneous wave-free ratio cutoff values for nonculprit stenosis classification in patients with ST-segment elevation myocardial infarction (an iSTEMI substudy). - Thim, T (2020)
OBJECTIVES: The instantaneous wave-free ratio cutoff value of <0.90 for hemodynamic significance of coronary stenoses has been validated in stable patients. We examined different cutoff values in the evaluation of nonculprit stenoses in patients with ST-segment elevation myocardial infarction. METHODS: We measured instantaneous wave-free ratio across nonculprit stenoses in the acute setting and at follow-up in 120 patients with ST-segment elevation myocardial infarction and 157 nonculprit stenoses, of which, 113 patients with 147 nonculprit stenoses completed follow-up. METHODS: The prevalence of nonculprit stenosis hemodynamic significance was 52% in the acute setting and 41% at follow-up. With follow-up, instantaneous wave-free ratio as reference, acute instantaneous wave-free ratio >0.90 had a negative predictive value of 89%. Acute instantaneous wave-free ratio <0.90 had a positive predictive value of 68%. Acute instantaneous wave-free ratio >0.93 had a negative predictive value of 100%. Acute instantaneous wave-free ratio <0.86 and <0.83 had positive predictive values of 71 and 77%. Using acute instantaneous wave-free ratio <0.90 as cutoff for hemodynamic significance yielded the highest degree of classification agreement between acute and follow-up instantaneous wave-free ratio. CONCLUSIONS: In patients with ST-segment elevation myocardial infarction, acute instantaneous wave-free ratio with the cutoff values <0.90 for hemodynamic significance appears optimal in the evaluation of nonculprit stenoses and has a high negative predictive value and a moderate positive predictive value.